2018
DOI: 10.1002/cbic.201800234
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Fluorination of Biotin and Tetrazine Conjugates for Pretargeting Approaches to Positron Emission Tomography Imaging

Abstract: The use of radiolabelled antibodies and antibody-derived recombinant constructs has shown promise for both imaging and therapeutic use. In this context, the biotin-avidin/streptavidin pairing, along with the inverse-electron-demand Diels-Alder (iEDDA) reaction, have found application in pretargeting approaches for positron emission tomography (PET). This study reports the fluorinase-mediated transhalogenation [5'-chloro-5'-deoxyadenosine (ClDA) substrates to 5'-fluoro-5'-deoxyadenosine (FDA) products] of two a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
0
9
0
4
Order By: Relevance
“…To date [ 18 F]-Fluoride incorporation has largely focussed on two-step enzymatic reactions using 5'-ClDA analogues and L-Met as a cofactor. [17][18][19][20][21][22][23]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date [ 18 F]-Fluoride incorporation has largely focussed on two-step enzymatic reactions using 5'-ClDA analogues and L-Met as a cofactor. [17][18][19][20][21][22][23]…”
Section: Discussionmentioning
confidence: 99%
“…The substrate flexibility of this 'two-step' fluorination process extends to 2'-deoxy analogues 16 of 5'-ClDA 1 as well as C-2 decoration of the adenosine base of 5'-ClDA 1 with an acetylene, or terminally functionalised acetylene moieties. [17][18][19][20][21][22][23] In this manner, fluorinase-mediated transhalogenation reactions have become established as a strategy for the synthesis of fluorinated bioactive compounds under experimentally benign conditions (ambient temperatures in buffer at pH 7.8). In particular, the method has been utilised for the late-stage 18 Fradiolabelling of cancer relevant targeting peptides [17][18][19][20][21] and A2A adenosine receptor agonists 23 for use in positron emission tomography (PET).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, different pre-targeting strategies have been developed for treatment and imaging of different diseases. Those include e.g., radiolabeling of the human A2A adenosine receptor [169], a prostate cancer-related membrane protein [170] or the combined application of biotin and tetrazine-conjugate with antibodies [171]. In all cases, it was shown that the fluorinase (FlA) accepts substrates with different moiety at C-2 of the adenine ring.…”
Section: Metal-free Haloperoxidases/perhydrolasesmentioning
confidence: 99%
“…Furthermore, conventional HPLC methodology can be used to separate non-radiolabelled starting material from radiolabelled p r o d u c t , regardless of the targeting scaffold tethered to the fluorinase binding motif. To date, this late-stage enzymatic 18 F-radiolabelling has been accomplished with cancer targeting pegylated RGD peptides, [38][39][40] A2A adenosine receptor agonists, 41 as well as tetrazine and biotin motifs, 42 for use as radiotracers in PET. For this study we have designed and synthesised a ClDA-PEG-GUL 15 construct to be used as a novel substrate for the fluorinase enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of the 5′chlorodeoxy-2-iodo-adenosine 11 was achieved via a five-step protocol using previously established methods 39 and the alkyne/protected car-boxylate functionalised linker 10 was obtained via a two-step process. 42 With 7, 10 and 11 in hand, their assembly was addressed. Firstly 10 and 11 were combined via a Sonogashira cross-coup-ling reaction, which, after successive flash chromatography and C18 cartridge purification, afforded 12 in good yield.…”
Section: Introductionmentioning
confidence: 99%